2020
DOI: 10.1177/0047287520981135
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and the COVID-(Mis)infodemic

Abstract: In addition to being formally defined as a pandemic, COVID-19 has been classified as an “infodemic” and “(mis)infodemic.” As an “infodemic,” the information environment on COVID-19 is constantly evolving, with emerging scientific findings, political responses, media coverage, and individual impressions all shared on social media. Initial positions on behaviors and potential treatments were presented and then discarded because of low efficacy or improper research procedures. Further, there has been a fragmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…A surprisingly high number of the LCG members (29%) indicated that they would never take a COVID-19 vaccine. This suggests not only a relationship between vaccine history and COVID-19 vaccine confidence but might also hint at ideological positions or overall misinformation at the base of lower confidence which can influence risk perceptions and efficacy perceptions (Williams et al, 2020). These might be especially important factors to consider as those individuals might be hard to convince to undertake the vaccine, which might jeopardize the success of the vaccination campaign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A surprisingly high number of the LCG members (29%) indicated that they would never take a COVID-19 vaccine. This suggests not only a relationship between vaccine history and COVID-19 vaccine confidence but might also hint at ideological positions or overall misinformation at the base of lower confidence which can influence risk perceptions and efficacy perceptions (Williams et al, 2020). These might be especially important factors to consider as those individuals might be hard to convince to undertake the vaccine, which might jeopardize the success of the vaccination campaign.…”
Section: Discussionmentioning
confidence: 99%
“…Milano et al, 2011;Xiang & Gretzel, 2010), issues related to misinformation appear relatively limited in the current pandemic context (Rather, 2021). Williams et al (2020) hypothesize that with the release of the COVID-19 vaccines, attitudes towards the vaccine take-up could have significant impacts on travel intentions. Accordingly, tourists may gravitate towards destinations that adopted a certain type of vaccine, certain types of rules and restrictions, and countries that are more or less vaccine-hesitant in their policies (p. 2).…”
Section: Protection Motivation Theory and Covid-19 Vaccinationmentioning
confidence: 99%
“…The hospitality and tourism businesses have been undergoing a severe crisis ever since the coronavirus disease (COVID-19) outbreak ( Bajrami et al, 2021 ; Bufquin et al, 2021 ; Chua et al, 2020 ; Williams et al, 2020 ). The airline industry has been especially hard-hit by the pandemic, leading to a steep drop in financial performance as well as an increase in employee career turnover ( Abate et al, 2020 ; Pereira & De Mello, 2021 ; Sobieralski, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A sharp decline in international air traffic, empty sea-beaches, and football matches without spectators are the visible indications. Moreover, mandatory vaccination is not acceptable to all, and inadequate or false information about COVID related rules and regulations also impact the industry [29]. However, after the COVID-19 pandemic, the world is likely to witness a considerable rise in tourism growth, which could help nations recover from economic crises.…”
Section: Introductionmentioning
confidence: 99%